Contact-free inactivation of Trichophyton rubrum and Microsporum canis by cold atmospheric plasma treatment. (September 2013) - Heinlin, Julia; Maisch, Tim; Zimmermann, Julia L; Shimizu, Tetsuji; Holzmann, Thomas; Simon, Michaela; Heider, Judith; Landthaler, Michael; Morfill, Gregor; Karrer, Sigrid
Aim: Cold atmospheric plasma (CAP) has already proven efficient at disinfection of microorganisms including biofilms. The objective of the present study is to assess the efficacy of CAP against the dermatophytes Trichophyton rubrum and Microsporum canis in vitro .Materials & methods: T. rubrum and M. canis were exposed to CAP for different treatment times and time intervals in vitro . Treatment with ciclopirox olamine or UVC radiation (0.120 J/cm 2 ) served as controls. CAP was generated by the surface microdischarge technology. Fungal colony growth was measured upon CAP treatment.Results: Repeated daily CAP treatments of 10 min demonstrated an inhibition of growth during the treatment period of 9 days. Single CAP treatment sessions for 5, 8 and 10 min, as well as treatments for 5 or 8 min daily, resulted in less fungal growth inhibition. UVC radiation treatment failed, but not ciclopirox olamine.Conclusion: CAP shows promising potential for future application in the treatment of dermatophyte infections.